OCT Analysis in Patients with Relapsing-Remitting Multiple Sclerosis during Fingolimod Therapy: 2-Year Longitudinal Retrospective Study - Settimio Rossi; Carlo Gesualdo; Antonio Gallo; Paolo Melillo; Francesco Martines; Raffaella Colucci; Alessandro d’Ambrosio; Gioacchino Tedeschi; Francesca Simonelli (Applied Sciences, 2020)
Many studies have demonstrated the usefulness of some optical coherence tomography (OCT) parameters, like total macular volume (TMV) and retinal nerve fiber layer thickness (RNFL-T), for monitoring patients with multiple sclerosis (MS). However, there are no real-world, long-term studies on patients with relapsing-remitting MS (RR-MS) treated with fingolimod. Therefore, the purpose of this study was to describe retinal changes associated with fingolimod therapy during a two-year follow-up while considering previous episodes of optic neuritis (ON). Patients diagnosed with RR-MS and treated with fingolimod (46 in total) underwent a two-year follow-up. Based on previous ON history, we identified 16 ON+ and 30 ON− patients. The ophthalmological evaluations, including visual field (VF) examination and OCT, were performed at a baseline at 3–6, 12 and 24 months to evaluate the progression rate for each parameter. When analyzing the whole sample, OCT showed no cases of macular edema. Instead, we observed a significant reduction rate in the central retinal thickness (CRT) (p < 0.001), TMV (p < 0.001) and RNFL (p < 0.05). Moreover, we observed a significant difference in the progression rate between ON+ and ON− patients, relative to the VF and RNFL (p < 0.05) examinations. OCT highlighted a significant progression rate of retinal damage in MS patients despite fingolimod therapy, especially in MS ON+ patients.